PENINGKATAN KINERJA SUMBER DAYA MANUSIA MELALUI IMPLEMENTASI MODAL PSIKOLOGI DAN KUALITAS KEHIDUPAN KERJA DI UNIT PELAYANAN KABUPATEN JEPARA - Farid Akhadah (Jurnal Riset Bisnis Indonesia, 2014)
This research aims to analyze the human resource performance through psychology capitalimplementation and quality of work life and examine the effect of psychology capital to humanresource performance which moderates the organizational service climate in service unit of BPMPPTand DPPKAD Jepara-Central Java, and the difference of psychology capital, quality of work life,organizational service climate and performance among service. The analysis technique is doneby using Partial Least Square (PLS) and t-test. The Results show that psychology capital has apositive significant influence on the quality of work life of and has a positive significant impact on theperformance, but quality of work life has no influence on the performance and there no influence oforganizational service climate in moderating performance. Result of t-test mean indicate that thereis difference of psychology capital among human resource service of service unit BPMPPT andDPPKAD Jepara, and there is a difference in organizational service climate among human resourceservice of service units of BPMPPT and DPPKAD Jepara, but there is no quality difference of worklife of among human resource service of service units of BPMPPT and DPPKAD Jepara, and thereno difference of performance of human resource service of service units of BPMPPT and DPPKADJepara.Keywords: psychology capital, quality of work life, organizational service climate, and humanresource performance.